2022
DOI: 10.1002/celc.202200093
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Vacancy‐Enhanced Ternary Nickel‐Tungsten‐Cerium Metal Alloy‐Oxides for Efficient Alkaline Electrochemical Full Cell Water Splitting Using Anion Exchange Membrane

Abstract: Alkaline water electrolysis is an attractive hydrogen generation technology with ultra‐high purity products and zero carbon emissions. However, the sluggish kinetics of oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) in both electrodes highly limits their applications. Benefiting from the abundant accessible active sites of the ternary alloy‐oxide structure formed on Ni foam directly, NiCeWOx shows superior HER and OER catalytic performances. The NiCeWOx‐2 (Ce/W ratio with 5/95) displays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…The overall water-splitting performance of the CWA//CWA cell is compared with recently reported cobalt and tungsten-based bifunctional catalysts which are used for overall water splitting (Figure d and Table S3). Figure e,f shows the optical image of overall water splitting of the CWA//CWA cell at 2.75 V potential and reveals that vigorous gas (both H 2 and O 2 ) evolutions were produced and released from the surface of the electrode.…”
Section: Resultsmentioning
confidence: 99%
“…The overall water-splitting performance of the CWA//CWA cell is compared with recently reported cobalt and tungsten-based bifunctional catalysts which are used for overall water splitting (Figure d and Table S3). Figure e,f shows the optical image of overall water splitting of the CWA//CWA cell at 2.75 V potential and reveals that vigorous gas (both H 2 and O 2 ) evolutions were produced and released from the surface of the electrode.…”
Section: Resultsmentioning
confidence: 99%
“…Electrical impedance spectroscopy (EIS) spectra and Tafel plots were recorded to study the 4e – OER kinetics of the copolymer electrocatalysts. , These kinetics are moderated by the rate-determining step (Scheme ), which is related to the electrocatalyst used. The obtained Nyquist plots were fitted with the Amstrong–Henderson model circuit (Figure S6); this includes the solution ( R s ) and charge transfer ( R ct ) resistances with a smaller arc radius, which corresponds to the effective transfer of charges with low R ct between the electrolyte and electrode.…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8] The scientists found that under alkaline conditions, even the most active Pt-based catalyst, HER/OER/ AOR kinetics is 2 to 3 orders of magnitude slower than that under acidic condition. [9][10][11] Great efforts have been made to develop highly active and stable electrocatalysts in neutral or alkaline conditions, for its importance in large-scale water hydrogen production or alkaline membrane fuel cell industry. [12][13][14] Although Pt-based materials usually possess the best electrochemical catalytic activity, the scarcity and towering cost hamper their widespread application.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, it is more difficult for most of the electrocatalysts to produce hydrogen or oxygen, even oxidize alcohol in neutral or alkaline conditions, mainly because of the sluggish decomposition kinetics [6–8] . The scientists found that under alkaline conditions, even the most active Pt‐based catalyst, HER/OER/AOR kinetics is 2 to 3 orders of magnitude slower than that under acidic condition [9–11] . Great efforts have been made to develop highly active and stable electrocatalysts in neutral or alkaline conditions, for its importance in large‐scale water hydrogen production or alkaline membrane fuel cell industry [12–14] .…”
Section: Introductionmentioning
confidence: 99%